ANALYSIS OF THE EFFECT OF JOB BURNOUT AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE MEDIATED BY CYBERLOAFING BEHAVIOR - Ramdani Ramdani; Dikdik Harjadi; Lili Karmela Fitriani; Dede Djuniardi; Odang Supriatna (Journal of Social Research, 2024)
This research aims to determine and analyze job burnout on employee performance; to determine and analyze organizational commitment to employee performance; to find out and analyze job burnout regarding cyberloafing; to determine and analyze organizational commitment to cyberloafing; to find out and analyze cyberloafing on employee performance; to find out and analyze cyberloafing mediating the relationship between job burnout and employee performance; to find out and analyze cyberloafing mediating the relationship between organizational commitment and employee performance. The research approach used by researchers in this research is a quantitative approach with descriptive and verification methods to prove the research hypothesis. The population used is all staff as total of 112 employees of PT. Shou Fong Lastindo. The sampling technique uses convenience sampling. Convenience sampling is a collection of information from members of the population that is easy to obtain and is able to provide that information. The analysis tool used is SEM-PLS. The research results show that there is a negative influence of job burnout on employee performance; there is a positive influence of organizational commitment on employee performance; there is a positive influence of job burnout on cyberloafing; there is a positive influence of organizational commitment on cyberloafing; there is a positive influence of cyberloafing on employee performance; cyberloafing mediates the effect of job burnout on employee performance; cyberloafing mediates the influence of organizational commitment on employee performance.